Interplay Among Physical Characteristics Play Position And Shooting Accuracy Of Elite-Female Basketballers (Department of Physical Education, Sport, Health and Recreation, 2018)
Abstract Physical characteristics are often considered to exert profound influence on playing position and shooting ability in basketball. The study examined interplay of physical characteristics, play position and shooting accuracy among female basketballers. Based on coaches’ rating, first 15 players were sampled but only 14 completed the measurements. The research design was descriptive correlation. Players’ bio-data were collected; height and weight were measured and BMI calculated. Research protocol included warm up and trials of 10 shots from three familiar distances. Participants were video recorded taking 30 shots in three blocks of 10 shots for each of the shooting distances. Descriptive statistics; percentage, ranking and mean were useds while PPMC and ANOVA were conducted to establish statistical significance at p ≤ 0.05. The players had high shooting accuracy which had no significant correlation with height, weight and BMI. Playing positions had no significant influence on shooting accuracy F2.74m (2, 11) = 1.085, p = .372; F4.67m (2, 11) = 0.535, p = .600; F6.40m (2, 11) = 0.884, p = .441. Shooting accuracy was not determined by only physical characteristics and playing position. Therefore, we recommend shooting performance at three distance zones during training, talent hunting and team selection.